The Proliferation of Digital Credit Deployments - Hwang, Byoung-Hwa; Tellez, Camilo (World Bank, Washington, DC, 2016)
This brief provides an introduction to the fast-evolving landscape of digital credit and illustrates common features of this new digital finance offering. The focus is on digital credit services that leverage customers’ existing access to a mobile phone, though there are also digital credit models building on a person’s connection to the internet. This brief uses 10 case examples to describe the digital credit trend, recognizing that there are many more pilots and products under design than are covered. Many of the case examples are new and have not reached scale yet, while a few already have portfolios reaching 800,000 to 1.8 million active borrowers.